1981
DOI: 10.1111/j.1399-3054.1981.tb05037.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin interaction with free radical metabolism and senescence: Effects on endogenous lipoxygenase and purine oxidation

Abstract: 1981. Cytokinin interaction with free radical metabolism and senescence: Effects on endogenous lipoxygenase and purine oxidation. -Physiol. Plant. 53: 9-12.A typical system comprising xanthine-xanthine oxidase, which produces superoxide free radicals, significantly increased endogenous levels of the seneseence-associated hpoxygenase enzyme while cytokinin reversed this effect. It is suggested that in its interaction with free radicals cytokinin may have a dual effect: a) it may inhibit purine oxidation by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
3

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 14 publications
1
22
0
3
Order By: Relevance
“…Linoleic acid is a constituent of plant membranes, and the association of ethylene production with membranes was noted above. Leshem has shown that the activity of lipoxygenase in pea leaves increases greatly during senescence and that cytokinins decrease its level in leaves (19,20); these findings give support to the idea of a parallel betweel senescence and the lipoxygenase system. The presence of lipoxygenase in the etiolated pea shoots is proven by the great decrease in the liberation of ethylene by the extract when linoleate is omitted (Table 4).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Linoleic acid is a constituent of plant membranes, and the association of ethylene production with membranes was noted above. Leshem has shown that the activity of lipoxygenase in pea leaves increases greatly during senescence and that cytokinins decrease its level in leaves (19,20); these findings give support to the idea of a parallel betweel senescence and the lipoxygenase system. The presence of lipoxygenase in the etiolated pea shoots is proven by the great decrease in the liberation of ethylene by the extract when linoleate is omitted (Table 4).…”
Section: Discussionmentioning
confidence: 66%
“…Unless otherwise stated, the reaction mixture contained 1 mM ACC, 1 mM linoleic acid, 0.1 mM MnCl2, 0.1 mM pyridoxal phosphate (pyridoxal-P), and 10 mM sodium [4-(2-hydroxyethyl)-1-piperazinepropanesulfonate (NaEPPS) buffer (pH 8.0). To this, 20 10,000 x g for 20 min. The supernatant was then centrifuged at 100,000 x g for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…134 It has been shown that cytokinins inhibits the activity of xanthine oxidase, one of the cellular free radical sources, and also act as a direct free radical scavenger. 135 Gidrol et al…”
Section: Staxen and Bornmanmentioning
confidence: 99%
“…Cytokinins also take part in the regulation of plant response to stress (Georgiev et al 1992, which may be the result of their possible function as antioxidants (Leshem et al 1981). Georgiev et al (1992) reported a strong protective effect of phenylurea cytokinin 4-PU-30 on marrow (Cucurbita pepo var.…”
mentioning
confidence: 99%